PELATIHAN UJI KOMPETENSI KEAHLIAN OTOMATISASI TATA KELOLA ADMINISTRASI PERKANTORAN - Endah Dewi Purnamasari; Leriza Desitama Anggraini (Politeknik Negeri Sriwijaya, 2021)
Expertise Competency Test is a test/test of expertise in a field that has been previously taken and studied. Expertise Competency Test or usually abbreviated as UKK, is one part of the Regulation of the Minister of Education and Culture. No. 34 of 2018, which has the objective of assessing learning outcomes. The target of this program is students majoring in Office administration. Skills Competency Test has the same purpose and purpose, namely to find out how skilled the students are following their majors as measured by the assessment and shows the results that the students are said to be competent if they pass the evaluation successfully. This community service activity aims to support the readiness of Vocational High School students for the Office Administration Automation program. Based on the results of the training activities, the results show that there is an increase in knowledge about the Expertise Competency Examination after conducting the training, which is demonstrated through the questionnaire distribution.